Uwarunkowania napływu kapitału zagranicznego do Polski - Kociszewska, Irena; Kamińska, Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article contains the values of global FDI flows and descriptions of the largest FDI providers and recipients. It also presents research on investment attractiveness of regions and countries. It describes favourable and limiting factors influencing the inflow of foreign capital to Poland. The main conductive factors are Poland's geographical location, market size, and labour costs; the major impediments are, however, susceptability to corruption, poor road infrastructure and bureaucracy. The opportunity for expanding foreign investment inflows is the policy of drawing advanced technologies to Poland and production specialization, e.g. electronics production. Nevertheless, despite good current results of foreign capital inflow to Poland, we need to take into consideration global trends towards locating investments in other regions of the world.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 226-239